A Matching Study on the Influence of Advertised Information Expression and Product Type on Consumer Purchase Intention - Yang, Qiang; Liu, Shanshan; Li, Yao; Kang, Haifeng (Frontiers in Psychology, 2022)
Due to extensive product differentiation and the personalized aesthetic needs of consumers, modern enterprises need different expressions of information to attract consumers’ interest and improve their purchase intention. This study draws from the elaboration likelihood model, anchoring theory, and media richness theory to explore how the expression of advertised information can be effectively matched to the product type to enhance consumers’ purchase intention. The mediating effect of information- processing fluency and moderating effect of consumers’ personal involvement on this relationship is also explored. Data from experiments and questionnaires involving 1,292 participants were analyzed. The results show that direct expression of advertised information are more suitable for advertising search products, while metaphorical expressions of advertised information are more suitable for advertising experience products. These combinations of product type and expression of advertised information can effectively improve consumers’ purchase intention. Meanwhile, the main combined effect of the product type and expression of advertised information is mediated by consumers’ information-processing fluency, and moderated by consumers’ personal involvement positively.